All Days 2010
DOI: 10.2118/135875-ms
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach to Mitigate Gas Production in a High GOR Carbonate Reservoir With Drilled Wells—Case Study

Abstract: Improving oil production is one of the most challenging subjects in carbonate reservoirs, especially in the case of thin formations when reservoir pressure is close to saturation pressure with undesired well locations. In this study water injection was used to mitigate gas production in a thin reservoir with high gas oil ratio for the purpose of optimizing oil production. The studied field is a cretaceous oil bearing reservoir composed of tightly packed limestone characterized by high porosity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…(2) 压裂液的低返排率和钻井完井过程中的工作 液侵入所造成的水相圈闭损害 [40,41] , 一定程度上制约 了页岩气的最终产出能力 液侵入速度. 根据Gallegos等人 [43] 对2014年美国数千口 页岩气水平井的统计, 水力压裂过程中进入储层中的 平均液量为19425 m 3 , Horn等人 [44] 的统计表明, 美国 页岩气井的压裂液返排率通常介于35%~62%, 而Che-kani等人 [45] 的分析认为页岩气井的返排率更低, 通常 http://engine.scichina.com/doi/10.1360/N092017-00202…”
Section: 当前的开发实践表明 页岩气产能与压裂形成的裂缝unclassified
“…(2) 压裂液的低返排率和钻井完井过程中的工作 液侵入所造成的水相圈闭损害 [40,41] , 一定程度上制约 了页岩气的最终产出能力 液侵入速度. 根据Gallegos等人 [43] 对2014年美国数千口 页岩气水平井的统计, 水力压裂过程中进入储层中的 平均液量为19425 m 3 , Horn等人 [44] 的统计表明, 美国 页岩气井的压裂液返排率通常介于35%~62%, 而Che-kani等人 [45] 的分析认为页岩气井的返排率更低, 通常 http://engine.scichina.com/doi/10.1360/N092017-00202…”
Section: 当前的开发实践表明 页岩气产能与压裂形成的裂缝unclassified
“…To obtain economical production, it is crucial to drill a horizontal well and implement multistage hydraulic fracturing to form a complex fracture network and to increase the contact area between the fracture surface and matrix. Although the characteristics of fracturing fluid flowback among different shale reservoirs are not the same, the flowback efficiency of a shale gas well is generally low. A large amount of retained fracturing fluid in a shale reservoir not only have a significant influence on gas flow, which greatly restricts the reservoir stimulation effect, but also induce potential contamination of groundwater. , Formation damage caused by fracturing fluid retention is mainly reflected as aqueous phase trapping (APT) damage . The formation process of APT damage could be divided into three main stages: (1) at the initial stage, the external aqueous phase has not entered the reservoir yet.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with hydraulic fracturing in conventional reservoirs, hydraulic fracturing in shale reservoirs is characterized by the low flowback efficiency of fracturing fluid, thus resulting in the retention of large amounts of fracturing fluid in shale formation . After investigating large amounts of production data on shale reservoirs, it is found that the flowback efficiency of the fracturing fluid is only between 10% and 40%. , The retarded fracturing fluid significantly increases the water saturation in the vicinity of the fracture surfaces, thus resulting in the blockage of gas flow and reduction of postfracturing productivity. When water saturation is close to 40%∼50%, gas well production will be seriously damaged .…”
Section: Introductionmentioning
confidence: 99%